Effect of Kasni seed preparations on serum glutamic pyruvic transaminase and glutamic oxaloacetic transaminase levels in newly diagnosed patients of type 2 diabetes mellitus - Katiyar, Praveen; Kumar, Amod; Mishra, Arvind K.; Dixit, Rakesh K.; Gupta, Ajay K. (International Journal of Research in Medical Sciences, 2017)
Background: Kasni (Cichorium intybus L.) reported to play an important role in the effective management of serum liver enzymes SGPT & SGOT in various animal models and this study is extension to newly diagnosed patients of type 2 diabetes mellitus. Methods: Newly diagnosed 90 patients of Type2 DM, age 35-65years, of either sex were divided into 3 groups. In group I only Metformin sustained release once a day and in group II/III 6 grams crude seed powder or 50 ml decoction of crude seed powder was given twice a day for 90 days in combination with Metformin sustained release orally once in a day. Serum liver enzyme levels of SGPT & SGOT were measured at zero, 30th, 60th and 90th day. Results: All the three groups showed a significant reduction in SGPT & SGOT across the four time periods. Post hoc Tukey HSD test shown that there was a significant difference between group I & II (p=0.011) and group I & III (p=0.000) for SGPT and group I & II (p=0.012) and group I & III (p=0.000) for SGOT. Conclusions: The add on therapy with Kasni seed preparations is more effective for the management of altered SGPT and SGOT levels in Type2 diabetes mellitus patients than only oral hypoglycaemic agent in decreasing SGPT & SGOT of selected patients. Among Kasni seed preparation treated groups, decoction was found more effective than crude seed powder.